RETRACTED ARTICLE : Comparison of supraglottic airway device vs. endotracheal intubation for initial airway management in out-of-hospital cardiac arrest: a systematic review and meta-analysis - Tao, Yan; Zhang, Juxia; Feng, Lei (Expert review of medical devices, 2025)
Out-of-hospital cardiac arrest (OHCA) is characterized by the cessation of mechanical cardiac activity and voluntary circulation occurring outside of a hospital setting, making it the leading cause of death worldwide. Recently, the optimal approach to airway management has been a subject of controversy. Follow PRISMA guidelines for systematic evaluation and meta-analysis. The primary outcome was survival assessed by four measures: Restoration of spontaneous circulation, survival to hospital or emergency department, evaluation of functional recovery after PCR (measured at both discharge and 3 months after PCR), and neurological function score at discharge. A total of six RCTs (14,205 patients) were included in the systematic review, and four RCTs (13,053 patients) were included in the meta-analysis. Five studies (83.3%) of RCTs with ETI controls were notable for their high quality, with low risk of bias judged in all 7 domains of the risk assessment scale. Showed an advantage of SGA (compared to ETI) with potential for ROSC (95% CI [1.02 to 1.18], I = 48%, = 0.01) and survival to hospital or emergency department (95% CI [1.01 to 1.17], I = 12%, = 0.02). This systematic review and meta-analysis found a significant association between SGA and the possibility of obtaining ROSC and reaching the hospital or emergency department after CPR in OHCA.